Dispensasi Nikah Dalam Penetapan No. 1234/Pdt.P/2020/Pa.Pra Ditinjau Dari UU No. 16 Tahun 2019 Tentang Perubahan Atas UU No. 1 Tahun 1974 Tentang Perkawinan - Wilia Sapitri, Siska; Munandar, Aris; Hadi Adha, Lalu (Private Law, 2023)
This researchâ€™ aim was to analyses judgeâ€™s consideration on marital dispensation as accommodated in the Determination Number 1234/Pdt.P/2020/PA.Pra viewed from the perspective of Law Number 16 of 2019 on the Amendment of Law Number 1 of 1974 on Marriage and to analyze what is the â€œurgent reasonâ€ in the determination. This research applied normative juridical approach. Result of the study shows that in principle judgeâ€™s consideration if the child applicant was not married will cause negative impact in the future. This urgent reason as judgeâ€™s consideration are: readiness to settle down, have established long-standing relationships, and have the ability to do so.